An assessment of the Arctic Ocean in a suite of interannual CORE-II simulations. Part II: Liquid freshwater. (March 2016) - Wang, Qiang; Ilicak, Mehmet; Gerdes, Rüdiger; Drange, Helge; Aksenov, Yevgeny; Bailey, David A; Bentsen, Mats; Biastoch, Arne; Bozec, Alexandra; Böning, Claus; Cassou, Christophe; Chassignet, Eric; et al.
Highlights: Arctic liquid freshwater budget simulated in 14 CORE-II models is studied. The models better represent the temporal variability than the mean state. Multi-model mean (MMM) FW fluxes compare well with observations. MMM FWC shows an upward trend in the recent years, with an underestimated rate. FW flux interannual variability is more consistent where volume flux determines it. Abstract: The Arctic Ocean simulated in 14 global ocean-sea ice models in the framework of the Coordinated Ocean-ice Reference Experiments, phase II (CORE-II) is analyzed in this study. The focus is on the Arctic liquid freshwater (FW) sources and freshwater content (FWC). The models agree on the interannual variability of liquid FW transport at the gateways where the ocean volume transport determines the FW transport variability. The variation of liquid FWC is induced by both the surface FW flux (associated with sea ice production) and lateral liquid FW transport, which are in phase when averaged on decadal time scales. The liquid FWC shows an increase starting from the mid-1990s, caused by the reduction of both sea ice formation and liquid FW export, with the former being more significant in most of the models. The mean state of the FW budget is less consistently simulated than the temporal variability. The model ensemble means of liquid FW transport through the Arctic gateways compare well with observations. On average, the models have too high mean FWC, weaker upward trends of FWC in the recent decade than the observation, and low consistency in the temporal variation of FWC spatial distribution, which needs to be further explored for the purpose of model development.